Overview of scientific production on authority control in the context of Linked Data: a systematic mapping in Information Science journals - Oliveira, Leonardo Silva; Castro, Fabiano Ferreira de; Silva, Márcia Regina da (Em Questão, 2025)
This article presents an overview of the scientific production on authority control in the context of Linked Data in Information Science journals. Conducted as an exploratory study, the investigation employs systematic mapping and a bibliometric approach to build representative indicators of the studied Corpus. A total of 116 articles published between 2010 and 2024 were analyzed, with data extracted regarding the year of publication, journals, authors’ affiliations, languages, and keywords used. The results indicate that 2019 was the most productive year, with the United States, Italy, and Spain being the countries with the highest number of publications. English is the predominant language, followed by Italian and Spanish. The articles address the topic in conjunction with bibliographic description standards such as the Resource Description and Access and the Bibliographic Framework Initiative, conceptual models such as the Functional Requirements for Bibliographic Records and the Resource Description Framework, as well as ontologies and identity management systems like the Virtual International Authority File and the Open Researcher and Contributor ID. The research highlights the transition and adaptation of traditional authority control to the current cataloging context, analyzing its impact on information retrieval and the management of relationships between entities. It concludes that, although discussions are more advanced on the international scene, particularly in the United States, Italy, and Spain, there remains a significant gap in studies on the topic in Brazil.